Territory and Democratic Politics A Critical Introduction - Mazzoleni, Oscar (Palgrave Studies in European Political Sociology, 2024)
The book provides a comprehensive and updated introduction to concept of territory in the study of democratic politics. Territory plays a rather marginal role in the traditional conceptions of democracy that in many ways still prevail today. Democratic politics is often analysed from the point of view of its institutions, citizens and voters, while little is said about the territory through which it is expressed - at most it provides a broader perimeter or context of political and institutional action. The book offers, instead, an introductory theoretically-oriented discussion of crucial issues such as the genesis of state-nation, the transformation of democratic citizenship, the current borders' policies, the rising of territorial populism and the experience of 19-covid pandemic. This is an open access book.